Haematuria. Issue 12 (December 2016) - Davis, Abigail
Haematuria is the presence of red blood cells in the urine, it is classified into two types: visible and non-visible. Non-visible haematuria is considered significant if blood is detected in two-out-of-three urine samples taken 2 to 3 weeks apart. Common causes of haematuria in adults include urinary tract infection, exercise-induced haematuria, nephrological disease, bladder cancer and renal stones. Common causes of haematuria in children include hypercalciuria, IgA nephropathy and post-streptococcal glomerulonephritis. Patients with visible haematuria should be referred for investigation to exclude urological cancer. Patients with non-visible haematuria should have their blood pressure, urinary albumin-to-creatinine ratio and estimated glomerular filtration rate measured, to determine if they require onward referral to secondary care. The new National Institute for Health and Care Excellence guidelines for recognition and referral of suspected cancer identify those patients with haematuria that should be referred through the 2-week wait pathway.